STRATEGIC COMMUNICATION FOR EMPLOYEE ENGAGEMENT: LESSONS FROM HIGHER EDUCATION INSTITUTIONS IN SOUTHERN AFRICA - Letlatsa, Relebohile (International Journal of Research -GRANTHAALAYAH, 2023)
The researcher has observed that employees at Higher Education Institutions (HEIs) in Southern Africa are aware of the importance of strategic planning, hence the formulation of strategic plans, but the concern arises at the implementation thereof. Therefore, the paper assesses the extent to which HEIs in Southern Africa utilise strategic communication for engagement of employees for implementation of their institutional strategy. Purposive sampling was used to identify HEIs in Southern Africa. In addition to this, an exploratory research design was used to establish if the strategic plan existed in each institution, and to find out strategies used to implement the strategic plan. The researcher used the explorative study because of the curiosity and desire to understand the influence strategic communication has on the implementation of the strategy. Strategic plans for the HEIs under study were assessed in order to find out if they indicate engagement of the employees and whether there are particular strategic measures proposed to solicit input of the employees in both the development and implementation of the strategic plan. Strategic plans were analysed to assess the degree to which strategies are implemented in the institutions. The study not only indicates the drivers, best practices and lessons of a communication strategy, but also suggests that when the organisation takes a strategic approach to communication, communication becomes integral to the formulation and implementation of strategy. It further suggests best ways to implement strategic plan using a communication strategy.